Striking effect of carbon nanotubes on adjusting sc-CO2 foaming performance of PS/LLDPE blends and forming semi-open cellular structure. (20th October 2020) - Shi, Zhiyuan; Zhang, Shaofeng; Qiu, Jian; Li, Minggang; Xing, Haiping; Tang, Tao
Abstract: The effect of carbon nanotubes (CNTs) on the phase structure and foaming performance of PS/LLDPE blends during batch foaming of sc-CO2 was studied. It was found that the phase structure of PS/LLDPE = 50/50 blends with CNTs could be transformed from bi-continuous to sea-island morphology, when a sufficient quantity of CNTs nanofillers was added. As a result, the foaming ability of PS/LLDPE = 50/50 blends was improved effectively. Meanwhile, the critical value of CNTs for significantly improving the foaming ability of blends decreased slightly with the increase of foaming temperature. In contrast, for the PS/LLDPE blends with sea-island phase structure (such as 20/80), the addition of CNTs did not significantly change the morphology and foaming capacity of the blends. Very interestingly, the foam with semi-open cellular structure (meaning that there were small pores within the large cell wall) was obtained in the foamed PS/LLDPE blends after tetrahydrofuran (THF) etching PS phase. Benefiting from the interfacial channel effect formed by the presence of CNTs, the etching speed and efficiency of PS were significantly improved, and the size for the small pore on the cell wall could be adjusted by the content of PS dispersed phase in the PS/LLDPE/CNTs nanocomposites. Graphical abstract: Image 1 Highlights: The presence of CNTs changes the morphology of LLDPE/PS blends from bi-continuous structure to sea-island structure. The presence of enough amount of CNTs can improve the foaming performance of LLDPE/PS blends with bi-continuous structure. The foam with semi-open cellular structure is obtained in the foamed LLDPE/PS blends after THF etching PS phase.